DESIGN AND INTENSITY ANALYSIS OF PORTABLE ADVERTISEMENT CLEANING MACHINE - LI Hao; GE YanYan; TIAN ChenYao; LIU HaiMa; ZHU WenJie; XIAO MaoHua (Jixie qiangdu)
According to the demand of outdoor rubbish advertisement cleaning,the design idea of a portable garbage advertisement cleaning machine is put forward. Its structure and function are designed and analyzed. The cleaning machine is mainly composed of a floating brush,a guide rod and a box. Driven by electricity,the brush rotates at the speed of 3000 r / min.The static method is used to analyze the stress of the brush and the guide rod,the mathematical model of brush is established,and the optimum solution of brush size and motor power is obtained by using MATLAB. the three-dimensional solid model of the cleaning machine is established by pro / E,static and modal analysis of brush are completed using ANSYS. The results showed that the stress is less than the allowable stress,And the stiffness was preferably,it is satisfied to design requirements. It provided a new method and idea for the research of this kind of cleaning machine.